2016
DOI: 10.1021/acs.jpcc.6b02439
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Adatoms and Molecules with Single-Layer Arsenene Phases

Abstract: Recent studies have shown that arsenic can form single-layer phases in buckled honeycomb as well as symmetric washboard structures, named as arsenene. These structures are stable even in freestanding form and are nonmagnetic semiconductors in the energy range which is suitable for various electronic applications. In this study we investigated the adsorption of selected adatoms (H, Li, B, C, N, O, Al, Si, P, Cl, Ti, Ga, Ge, As, Se and Sb) and physisorption of molecules (H 2 , O 2 and H 2 O) to these two arse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 35 publications
5
53
0
Order By: Relevance
“…After the synthesis of very thin films of phosphorus [27] researchers started to seek similar structures in other group-V elements or pnictogens. Recent theoretical studies have predicted that nitrogen [28], phosphorus [29][30][31], arsenic [32][33][34][35], antimony [36][37][38][39], bismuth [40][41][42][43], and compounds of group-V elements [44] can form stable freestanding SL, planar as well as buckled honeycomb (b) structures similar to that of silicene and germanene and also other manifolds, such as SL symmetric (w) and asymmetric (aw) washboard structures, among others. These SL phases are named, respectively, nitrogene, phosphorene, arsenene, antimonene, and bismuthene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the synthesis of very thin films of phosphorus [27] researchers started to seek similar structures in other group-V elements or pnictogens. Recent theoretical studies have predicted that nitrogen [28], phosphorus [29][30][31], arsenic [32][33][34][35], antimony [36][37][38][39], bismuth [40][41][42][43], and compounds of group-V elements [44] can form stable freestanding SL, planar as well as buckled honeycomb (b) structures similar to that of silicene and germanene and also other manifolds, such as SL symmetric (w) and asymmetric (aw) washboard structures, among others. These SL phases are named, respectively, nitrogene, phosphorene, arsenene, antimonene, and bismuthene.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, we studied SL pnictogen phases consisting of planar and buckled honeycomb and symmetric and asymmetric washboard structures, whereby their dynamical and thermal stability, mechanical, electronic, magnetic, and optical properties were revealed and also their functionalization with selected single atoms and molecules was investigated [21,[34][35][36]43]. In those studies crucial effects of the structures on physical properties were revealed.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that these structures are stable against the long-wavelength displacements indicating the stability at T = 0 K. The predicted semiconducting character having a band gap in the range of 1.5-2.10 eV and other properties of arsenene have attracted considerable interest. Very recently, various theoretical studies contributed for better understanding of arsenene [10][11][12][13][14][15][16]. Promising progress towards the synthesis of these phases has also been reported [17].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse allotropes of arsenene have been studied more with a focus on their structural, mechanical, and electronic properties, where arsenene and antimonene were also found to display high carrier mobility, superior mechanical properties, negative Poisson's ratio, and possible topological phase transition features in themselves [19][20][21][22][23][24][25][26][27]. The layered three-dimensional (3D) phase of arsenic, i.e., gray arsenic, presents strong evidence that single-layer arsenic can exist as a local minima in the Born-Oppenheimer surface.…”
Section: Introductionmentioning
confidence: 99%